2016
DOI: 10.1136/bmjopen-2016-013241
|View full text |Cite
|
Sign up to set email alerts
|

Setting priorities for research in medical nutrition education: an international approach

Abstract: ObjectivesTo identify the research priorities for medical nutrition education worldwide.DesignA 5-step stakeholder engagement process based on methodological guidelines for identifying research priorities in health.Participants277 individuals were identified as representatives for 30 different stakeholder organisations across 86 countries. The stakeholder organisations represented the views of medical educators, medical students, doctors, patients and researchers in medical education.InterventionsEach stakehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
2
10
0
2
Order By: Relevance
“…In concordance with other studies, participants in this study appreciated the need for nutrition education but were less confident in their nutrition knowledge and clinical skills (Vetter et al, 2008;Sunguya et al, 2013;Ball et al, 2016;Perlstein et al, 2016). Students had the communication tools necessary to discuss nutrition with patients.…”
Section: Discussionsupporting
confidence: 67%
“…In concordance with other studies, participants in this study appreciated the need for nutrition education but were less confident in their nutrition knowledge and clinical skills (Vetter et al, 2008;Sunguya et al, 2013;Ball et al, 2016;Perlstein et al, 2016). Students had the communication tools necessary to discuss nutrition with patients.…”
Section: Discussionsupporting
confidence: 67%
“…However, few studies acknowledge the complex learning environment of medical training that involves strong elements of enculturation and normative behaviour 23. In line with this limitation, the degree to which medical students place an emphasis on nutrition during medical training has been identified as an important ongoing research question in the field 24…”
Section: Introductionmentioning
confidence: 99%
“…Poor nutrition is one of the most dominant lifestyle-related risk factors for chronic diseases [ 1 , 2 ] and has also been shown to have adverse effects on acute illnesses [ 3 ]. Epidemiological data show that seven out of the ten leading causes of death are chronic diseases that possess a critical nutrition component, such as heart disease, cancer and diabetes [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition care refers to any practice undertaken by a health professional to improve an individual’s food-related behavior and subsequent health outcomes [ 1 , 2 , 6 , 14 , 15 , 16 ]. Studies have shown that GPs can be very effective in enhancing patients’ nutrition behavior through the implementation of nutrition care [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%